Konsentrasi dan Motilitas Spermatozoa Ayam Kampung (Gallus domesticus) dalam Pengencer Ringer Laktat Yang Diberi Tambahan Minyak Buah Merah (Pandanus conoideus Lam) - Isnaeni, Mei; Faidiban, O R; Tethool, Angelina Novita (Fakultas Peternakan Universitas Papua, 2019)
Red fruit oil is a red fruit extraction product (Pandanus conoideus Lam) containing a lot of antioxidants such as carotenoids, tocopherols as well as unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid and decanoic acid which is potential to be used as an additive for semen chicken diluents. This study aims to obtain an information about the effectiveness of adding red fruit oil as a cement diluent derived from male native chickens. The treatment consisted of 0.9 ml ringer laktat + 0.1 ml semen (Pl), ringer laktat 0.98 ml + 0.1 ml semen + 0.02 ml red fruit oil (P2), ringer laktat 0.96 ml + 0.1 ml semen + 0.04 ml red fruit oil (P3), ringer laktat 0.94 ml + 0.1 ml cement + 0.06 ml red fruit oil (P4). The results showed the sperm motility ranged from 48.17 Â± 7.86% to 84.67 Â± 2.42%. Treatment P1 and P2 have a very significant difference (P <0.01) on motility 0.05). The spermatozoa concentration ranged from 1,600x106 cells / ml to 2,200x106 cells/ml. The spermatozoa concentration of treatment P1 and P2 chickens did not show any significant differences (P> 0.05), nor did among treatments P2, P3 and P4. However, treatment P1 has a significant difference on spermatozoa concentration with P3 and P4. (P <0.05). It can be concluded that the addition of red fruit oil in lactated ringer diluent can be used as an additive for semen diluents because it is able to maintain the concentration. In addition, adding of red fruit oil up to concentrations of more than 2% tend to reduce sperm motility. Keywords: Concentration, Motility, Spermatozoa and Red fruit oil